Prospective Biomarker Analysis of the Randomized CHER-LOB Study Evaluating the Dual Anti-HER2 Treatment With Trastuzumab and Lapatinib Plus Chemotherapy as Neoadjuvant Therapy for HER2-Positive Breast Cancer. (5th August 2015) - Guarneri, Valentina; Dieci, Maria Vittoria; Frassoldati, Antonio; Maiorana, Antonino; Ficarra, Guido; Bettelli, Stefania; Tagliafico, Enrico; Bicciato, Silvio; Generali, Daniele Giulio; Cagossi, Katia; Bisagni, Giancarlo; Sarti, Samanta; et al.
Abstract: Background: The CHER-LOB randomized phase II study showed that the combination of lapatinib and trastuzumab plus chemotherapy increases the pathologic complete remission (pCR) rate compared with chemotherapy plus either trastuzumab or lapatinib. A biomarker program was prospectively planned to identify potential predictors of sensitivity to different treatments and to evaluate treatment effect on tumor biomarkers. Materials and Methods: Overall, 121 breast cancer patients positive for human epidermal growth factor 2 (HER2) were randomly assigned to neoadjuvant chemotherapy plus trastuzumab, lapatinib, or both trastuzumab and lapatinib. Pre- and post-treatment samples were centrally evaluated for HER2, p95-HER2, phosphorylated AKT (pAKT), phosphatase and tensin homolog, Ki67, apoptosis, and PIK3CA mutations. Fresh-frozen tissue samples were collected for genomic analyses. Results: A mutation in PIK3CA exon 20 or 9 was documented in 20% of cases. Overall, the pCR rates were similar in PIK3CA wild-type and PIK3CA -mutated patients (33.3% vs. 22.7%; p = .323). For patients receiving trastuzumab plus lapatinib, the probability of pCR was higher in PIK3CA wild-type tumors (48.4% vs. 12.5%; p = .06). Ki67, pAKT, and apoptosis measured on the residual disease were significantly reduced from baseline. The degree of Ki67 inhibition was significantly higher in patients receiving the dual anti-HER2 blockade. The integrated analysis of gene expression and copy number data demonstrated that a 50-gene signature specifically predicted the lapatinib-induced pCR. Conclusion: PIK3CA mutations seem to identify patients who are less likely to benefit from dual anti-HER2 inhibition. p95-HER2 and markers of phosphoinositide 3-kinase pathway deregulation are not confirmed as markers of different sensitivity to trastuzumab or lapatinib. Implications for Practice: HER2 is currently the only validated marker to select breast cancer patients for anti-HER2 treatment; however, it is becoming evident that HER2-positive breast cancer is a heterogeneous disease. In addition, more and more new anti-HER2 treatments are becoming available. There is a need to identify markers of sensitivity to different treatments to move in the direction of treatment personalization. This study identified PIK3CA mutations as a potential predictive marker of resistance to dual anti-HER2 treatment that should be further studied in breast cancer. Abstract : HER2 is currently the only validated marker to select breast cancer patients for anti-HER2 treatment. There is a need to identify markers of sensitivity to different treatments to move in the direction of treatment personalization. This study identified PIK3CA mutations as a potential predictive marker of resistance to dual anti-HER2 treatment that should be further studied in breast cancer.